Identifikasi Isolat Antikanker Spons Hyrtios Erecta - SWANTARA, I MADE DIRA; RITA, WIWIK SUSANAH; HERNINDYA, ANISA (Indonesian Journal of Cancer, 2016)
ABSTRACTIsolation, anticancer activity test, and identification of the toxic isolate from ethanol extract of the sponge Hyrtios erecta taken from Pari Island beach (Jakarta) has conducted. Extraction of the sponges was carried out by 70% ethanol at room temperature. Partition and purification of the compounds were done by column chromatography with the stationary phase of silica gel and the mobile phase of n-hexane-chloroform (2:8). Toxicity screening test was done based on BhrineShrimp Lethality Test (BSLT). In vitro anticancer activity test of the isolate was carried out using HeLa cell line. Identification of the compounds was performed by Gas chromatography-mass spectroscopy (GC-MS). Based on theresults, it was found that the toxic isolate of H. erecta sponges has anticancer activity with IC50 of 30,497 ppm. Four compounds was detected from the anticancer isolate i.e: 4-nonylphenol; dibutyl phthalate; hexanedioic acid bis(2-ethylhexyl) ester; and cholesterol.Â ABSTRAKTelah dilakukan isolasi, uji aktivitas antikanker, dan identifikasi isolat toksik yang berasal dari ekstrak etanol spons Hyrtios erecta yang diambil dari perairan Pulau Pari (Jakarta). Ekstraksi dilakukan dengan cara maserasi menggunakan etanol 70% pada temperatur kamar. Pemisahan dan pemurnian komponen menggunakan kromatografi kolom dengan fase diam silikagel dan fase gerak n-heksana-kloroform (2:8). Skrining toksisitas dilakukan dengan metode Bhrine Shrimp Lethality Test (BSLT). Uji antikanker secara in vitro isolat toksik tersebut menggunakan sel HeLa. Senyawanya diidentifikasi menggunakan Gas chromatography-mass spectroscopy (GC-MS). Berdasarkan hasil penelitian ini diperoleh bahwa isolat toksik spons H. erecta bersifat antikanker dengan IC50 sebesar 30,497 ppm. Pada isolat antikankertersebut terdeteksi empat senyawa, yaitu 4-nonylphenol; dibutil phtalat; ester heksadioat bis(2-etilheksil); dan kolesterol.